Design and Development of 3-Axis Benchtop CNC Milling Machine for Educational Purpose - Abd Rahman, Zammeri; Mohamed, Saiful Bahri; Minhat , Mohamad; Abd Rahman, Zulkifli (International Journal of Integrated Engineering, 2023)
The main factor in improving learning skills is providing students with hands-on laboratory experience, and the small-scale machine can accomplish academic programs requiring students to learn machining skills. This paper aims to design and develop a 3-axis CNC milling machine with a PC-based open architecture controller in a vertical position open frame structure. Some technical specifications were randomly selected based on the capabilities of similarly sized machines reviewed in previous work. The designed machine consisted of inexpensive off-the-shelf hardware components capable of machining the sample block with high cutting speed and reasonable precision. The accepted percentage error of circular and straightness test readings is below the set requirements. This machine is not intended for series production and precise machining. It can still effectively replace the high cost of commercial CNC machines and be used in any higher education institution offering technical courses.